Skill differences in visual anticipation of type of throw in team-handball penalties - Loffing, L.; Hagemann, N. (Psychology of Sport and Exercise, 2014)
Objectives: Visual identification and anticipation of an opponent's action intentions is crucial for successful performance in interactive situations such as team-handball penalties. We conducted two experiments to examine experienced and novice team-handball goalkeepers' ability to predict the type of throw in handball penalties and to identify the observers' reliance on local versus globally distributed spatial cues. Design and methods: In Experiment 1, following a 2 (Skill) × 5 (Temporal Occlusion Condition) factorial design participants were provided with videos of team-handball penalties where the amount of viewing time was varied. In Experiment 2, another sample of experienced and novice goalkeepers watched videos of spatially manipulated penalties where specific parts of the thrower's body or the ball were either removed or presented in isolation (2 [Skill] × 9 [Display Condition] factorial design). Results: In Experiment 1, experienced goalkeepers outperformed novices and both groups similarly improved their performances with later occlusion conditions. In Experiment 2, experienced goalkeepers were again superior to novices, and local cues (e.g., ball and hand) were sufficient for better than chance predictions in both groups. Moreover, experienced in contrast to novice goalkeepers (i) suffered from the removal of and (ii) benefited from the addition of distal (i.e., throwing arm and ball) as well as proximal (i.e., upper body) kinematic features. Conclusions: Our research is in line with previous findings on perceptual-cognitive expertise in sports and suggests that experienced team-handball goalkeepers rely on multiple, globally distributed cues when making anticipatory judgments.